Mapping Europe's seismic hazard - Giardini, Domenico; Wössner, Jochen; Danciu, Laurentiu; id_orcid:0 000-0003-4086-8755 (American Geophysical Union, 2014)
From the rift that cuts through the heart of Iceland to the complex tectonic convergence that causes frequent and often deadly earthquakes in Italy, Greece, and Turkey to the volcanic tremors that rattle the Mediterranean, seismic activity is a prevalent and often life‐threatening reality across Europe. Any attempt to mitigate the seismic risk faced by society requires an accurate estimate of the seismic hazard. ISSN:0096-3941 ISSN:2324-9250